The Influence of Gender, Period of Study, and Morale of Lecturers and Staff on Students' Learning Motivation - Samsudin Samsudin; Bambang Budi Wiyono; Rohaida Binti Mohd. Saat; Khalip Musa; Arifin Arifin (Jurnal Pemberdayaan Masyarakat, 2025)
Various internal and external factors shape students' learning motivation. This research aims to examine how gender, length of study, and the morale of lecturers and administrative staff influence students' motivation to learn. An explanatory research design was employed, with the study population comprising students from Universitas Negeri Malang and Universitas Negeri Gorontalo. A total of 572 students were selected through a cluster random sampling method. Data were gathered using questionnaires and documentation, then analyzed through descriptive statistics, analysis of variance, and structural equation modeling. The findings reveal that students' learning motivation differs significantly according to gender and study period. Lecturers' morale has a notable impact, while staff morale does not show a significant effect. These results suggest that gender, study duration, and lecturers' morale contribute meaningfully to students' learning motivation. The novelty of this study lies in identifying these three aspects as key determinants of motivation, an area that has not been extensively investigated in previous research. This insight offers valuable implications for improving the quality of teaching and learning in higher education.